THE JAVANESE INTERFERENCE TOWARDS ENGLISH IN AL-AMANAH ISLAMIC MODERN COLLEGE - SETYOWATI, ENI (Language Horizon: Journal of Language Studies, 2014)
KajianiniditujukanuntukmenjelaskaninterferensidariBahasaJawakeBahasaInggris, lebihkhususpada area fonologi.Interferensipada area fonologiterjadijikaadaaspekdaribahasa lain padaucapanseseorang (Dulay di Rochmawati,2007:8). TujuandarikajianiniadalahuntukmemberikangambarandarifenomenainterferensidariBahasaJawakeproduksiucapanBahasaInggris.Cara pegungkapanparamurid di SMP AL – MANAH terutamaparasiswinyadapat di analisisdan di interpretasikansecaramendetailmelaluiteoriphonologi.Untukmemperoleh data, penelitimengunakanduametode; observasidan interview.Dalamobservasi, penelitimendekatiparasiswi yang sedangbercakap – cakapdanmerekampembicaraanmereka.Sementaraitu, penelitijugamenginterviewmerekadanlembar interview jugatermasukmenjadi instrument penelitian.Padaakhirnya, hasildaripenelitianmenunjukanbahwauntukbeberapakonsonandalambahasainggrisdan vowels Kata kunci:Interferensi, BahasaJawa, EjaanBahasaInggris Abstract This research is to reveal the interference of Javanese to English, especially in the area of phonology. Interference in phonology occurs if there are aspects of another language in one’s utterances (Dulay in Rochmawati, 2007, p.8). The aims of this research are to give an overview of the phenomena of the Javanese interference towards English production. The utterances of the students in Al-Amanah Islamic Modern College, especially the female students are analyzed and interpreted descriptively through the theory of Phonological rules. To collect the data, the researcher use two methods; observation and interview. In observation, the researcher come nearer to the students who having a conversation and record their utterances. While, the interview is also conducted and an interview sheet also considered as research instrument. Finally, the result of this research shows that there are some English consonants and vowels are interfered by the Javanese. The English consonants that interfere by the Javanese are: /ð/, /θ/, /z/, /v/, /d/, /k/, /?/, and /?/. The students are difficult to produce the sound /ð/, /θ/ and /?/. Then, the students also change some diphthong into a vowel; /æ/ into /e/, /au/ into /?/, /ai/ into /e/, and /au/ into /?/. Key Terms: Interference, Javanese, English Pronunciation